Prevalence of goiter and its association with iodine status among the women of reproductive age group in coastal villages of Udupi Taluk, Karnataka, India - T Sravan Kumar Reddy; Veena G Kamath; George P Jacob; Asha Kamath; Cleeta Rebeiro (Wolters Kluwer Medknow Publications, 2019)
Background: Iodine deficiency is one of the most prevalent micronutrient deficiencies globally. Women in reproductive age group are vulnerable to develop iodine deficiency as there is an increase in demand for iodine, especially during pregnancy. Objectives: The objective is to assess the prevalence of goiter and its association with iodine status and salt usage practices among the women of reproductive age group. Methods: A community-based cross-sectional study was conducted from August 2015 to July 2017 among 1500 women of reproductive age group in five villages of Udupi Taluk. Stratified sampling design and proportion to population size of the reproductive age women in the study area was used to select the study participants. A pretested semi-structured questionnaire was used for data collection. Goiter was assessed clinically and graded as per the recommended criteria of the WHO. Salt samples from every household were collected for iodine estimation. Blood and urine samples were collected from subsample to estimate thyroid-stimulating hormone levels and urinary iodine excretion levels, respectively. Results: The overall prevalence of goiter was 13% with 11.5% being Grade 1 and 1.5% being Grade 2. No significant association of goiter with urinary iodine, salt iodine levels, and salt usage practices was found. Conclusions: Median urinary iodine among the women with goiter indicates iodine sufficiency and no significant difference observed in urinary iodine levels between women with and without goiter.